A novel regulatory circuit underlying plant response to canopy shade - Carabelli, Monica (Landes Bioscience, 2008)
A plant growing in the field has the unique ability to sense the presence of other plants growing near by and adjust its growth rate accordingly. This ability to detect neighbors, which is referred to as shade avoidance response, is mediated by members of the phytochrome family which detect light in the red (R) and far-red (FR) region of the spectrum. Work done by several laboratories has shown that low R/FR provides the signal for shade avoidance response during which the elongation of stem-like organs occurs at the expense of leaf development. However, the mechanism by which the low R/FR signal is transduced to attenuate leaf development has remained largely unknown. In the August issue of Genes and Development, we have shown that low R/FR rapidly and transiently arrests the growth of the leaf primordium. By exploiting mutant analysis in combination with genome wide expression profiling, we have identified a novel regulatory circuit underlying plant response to canopy shade. Together, the data demonstrate that the growth arrest induced by low R/FR depends on auxin-induced cytokinin breakdown in pre-procambial cells of developing primordia. In this addendum, we discuss open questions to be addressed in the future.